Dynamics an introduction for civil and structural engineers - Maguire, J. R. (Thomas Telford, 2002)
The second edition of this best selling guide provides civil and structural engineers with introductory information on all the main principles and important aspects of the subject.
Previous ed.: 1999.
Keywords: Structural dynamics.; Structural engineering.; Civil engineering.; elektronické knihy; electronic books